209. Methicillin-Sensitive Staphylococcus aureus (MSSA) Septicemia-Outcomes of Ceftriaxone Compared with Cefazolin and Oxacillin Outpatient Therapy from a Large National Sample. (4th December 2021) - Hamad, Yasir; Nickel, Katelin B; Olsen, Margaret A; George, Ige
Abstract: Background: Ceftriaxone has activity against MSSA and is convenient to use during outpatient parenteral antimicrobial therapy (OPAT). We examined outcomes of MSSA septicemia on patients receiving cefazolin, ceftriaxone or oxacillin OPAT using administrative data. Methods: A large insurance claims database of privately insured patients (IBM MarketScan) aged 18 – 64 years from 2010 to 2018 was queried for patients with MSSA septicemia discharged from the hospital on cefazolin, ceftriaxone, or oxacillin OPAT. The primary endpoint was 90-day hospital readmission with same infection category as the index admission. Factors with significant association in univariate analysis were incorporated into a multivariable Cox proportional hazards model with sequential exclusion of variables with p > 0.1. Results: A total of 1, 895 patients were included; the median age was 54 years and 62.9% were male. Primary outcome occurred in 366 (19.3 %). Factors associated with readmission in multivariable analysis included older age (61-64 years) (aHR 1.42 [CI 1.02-1.98]), obesity (1.31 [1.04-1.65]), intensive care unit (ICU) stay during index MSSA hospitalization (2.11 [1.68-2.65]), hospitalization in the month prior to index MSSA (1.46 [1.15-1.85]), central line associated bacteremia (1.72 [1.26-2.35]), endocarditis (1.56 [1.19-2.04]) and prosthetic joint infection (1.77 [1.26-2.50]). There was no difference in infection-associated readmission among patients treated with ceftriaxone compared to cefazolin or oxacillin (Figure 1). Conclusion: Older age, ICU admission, obesity, endocarditis, and prosthetic joint infections were associated with increased risk of hospital readmission with infection following OPAT for MSSA septicemia. Treatment with ceftriaxone was not associated with worse outcomes compared to oxacillin or cefazolin. Figure 1. Kaplan Meier Survival Analysis for readmission free survival (log-rank P value 0.31) Disclosures: Margaret A. Olsen, PhD, MPH, Pfizer (Consultant, Research Grant or Support)